2022
DOI: 10.2147/ijgm.s380328
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Human Brucellosis and Risk Factors for Focal Complications: A Retrospective Analysis in a Tertiary-Care Hospital in Beijing, China

Abstract: Brucellosis is an ongoing zoonotic disease in China, but there are few data in Beijing. This study was designed to illustrate clinical characteristics of patients with brucellosis in Beijing, China and explore the risk factors for focal brucellosis. Patients and Methods: Data of patients with brucellosis were retrospectively collected from the patients' electronic medical records in Beijing Youan Hospital during 2010 to 2021, including epidemiological, demographic and clinical features. Risk factors for focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
(39 reference statements)
1
8
1
Order By: Relevance
“…Therefore, brucellosis should be considered in the differential diagnosis of osteoarthropathy, orchitis, and other physiotherapy-related diseases in the rehabilitation department, especially in endemic regions. The spectrum of clinical symptoms and the distribution of focal involvement were found to be different from previous studies [16][17][18]. In our study, the complicated group showed a significantly higher incidence of arthralgia, inappetence, nausea, orchialgia, and eye bulging pain, while fatigue was significantly less frequent compared to the uncomplicated group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, brucellosis should be considered in the differential diagnosis of osteoarthropathy, orchitis, and other physiotherapy-related diseases in the rehabilitation department, especially in endemic regions. The spectrum of clinical symptoms and the distribution of focal involvement were found to be different from previous studies [16][17][18]. In our study, the complicated group showed a significantly higher incidence of arthralgia, inappetence, nausea, orchialgia, and eye bulging pain, while fatigue was significantly less frequent compared to the uncomplicated group.…”
Section: Discussioncontrasting
confidence: 99%
“…Specifically, osteoarticular complications were more commonly seen in large joints, such as the spine. Our results align with previous studies, which also identified arthralgia, absence of myalgias, and low back pain as associated factors for complications [ 16 , 19 21 ]. Notably, eye bulging pain, although not common in brucellosis patients, should be carefully considered during diagnosis and treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, cardiac and neurological manifestations might make the diagnosis more challenging. 15 Clinical manifestations of our case were insidious fever, generalized pain, weakness and lethargy, anorexia, and headache.…”
Section: Discussionmentioning
confidence: 61%
“…Patients with brucellosis typically experience non‐specific symptoms such fever, night sweats, arthralgia, headache, fatigue, anorexia, myalgia, and weight loss. Additionally, cardiac and neurological manifestations might make the diagnosis more challenging 15 . Clinical manifestations of our case were insidious fever, generalized pain, weakness and lethargy, anorexia, and headache.…”
Section: Discussionmentioning
confidence: 80%
“…Following uptake by local tissue lymphocytes, Brucella can disseminate throughout the body via the lymphoreticular system or bloodstream, leading to potential damage to various organs or body systems. 2,12,13 Traditional culture methods for brucellosis typically require one to four weeks for detection. 14 Clinical manifestations of brucellosis are characterized by undulant fever, malaise, arthralgias, hepatomegaly, splenomegaly, lymphadenopathy, or focal involvement of specific organs such as the epididymis, joints, cardiovascular system, and central nervous system.…”
Section: Discussionmentioning
confidence: 99%